A Test of the Ricardian Equivalence Hypothesis for Nepal - Pandey, Bhanu Bhakta; Poudel , Priyanka (JMC Research Journal, 2020)
This study is undertaken to verify the application of Ricardian Equivalence Hypothesis (REH) for Nepal by using annual time-series data covering from 1975 to 2019. The study employs Augmented Dickey–Fuller unit root test, Engel Granger causality test, the long run multiple regression model, Error correction model (ECM) in estimating the systems equations to examine the objectives of the study. From the perspective of this study, the empirical findings demonstrated that the Ricardian Equivalence Hypothesis (REH) doesn’t hold for Nepal invalidating the proposition of the Ricardian Hypothesis.